Parametric Study and Experimental Validation of Acoustic Leaky Wave Antenna in Spatial Localization - Alejandro Fernandez-Garrido; Maria Campo-Valera; Elena Abdo-Sanchez; Ruben Pico; Antonio-Javier Garcia-Sanchez; Rafael Asorey-Cacheda (IEEE Access)
Acoustic signals, which have been utilized for decades in the spatial localization of objects, have found applications in fields as diverse as sonar for underwater navigation, communication, and object detection. Traditional methods often rely on arrays of transducers, which necessitate the use of expensive hardware and processing algorithms. An emerging alternative is the Acoustic Leaky Wave Antenna (ALWA), which is inspired by electromagnetic leaky wave antennas. ALWA technology employs a single transducer to emit directional beams that scan angular space by frequency manipulation. Conventional arrays offer cost-effectiveness and simplicity of design, but ALWAs have the advantage of operating on the principle of energy leakage, which is achieved by various mechanisms, such as uniform apertures or slits periodic along the waveguide. This technology, applicable to underwater and airborne communications, offers compact and energy-efficient solutions, which facilitate the development of the “Underwater Internet of Things” and autonomous communication systems for underwater vehicles. This work presents a parametric study of this type of antennas with axisymmetric geometry by means of a numerical solution based on the Finite Element Method. Together with analytical studies, the physical phenomenology underlying this technology will be described, including directivity, transmission and reflection parameters, beam scanning and dispersion curve. Finally, the design is validated through experiments.